Effects of size and apical or basal portions of the tiller on the morphology of elephant grass (Veterinária Notícias, 2018)
This work was developed to evaluate the effects of the size and the apicaland basal portions of the tiller on the morphology of elephant grass(Pennisetum purpureum cv. Napier). Two experiments were performed. Inthe first one, the characteristics were evaluated of basal tiller with foursizes (80, 120, 160 and 200 cm). A completely randomized design was used,with three replications. In the second experiment, the morphology of thebasal and apical portions, from small tillers (100 cm) and large (180 cm)elephant grass were evaluated. The design was completely randomizedand the split-plot scheme was used, with three replications. The numbersof living and dead leaves, stem and leaf lengths, leaf blade width, andtiller mass increased linearly with elephant grass size. The basal portionof the elephant grass tiller had a higher mass (56.2 g), higher percentagesof leaf dead (2.1%) and live stem (89.5%), and a lower percentage of liveleaf blade (23.4%) than the apical portion. With the increase in size, theelephant grass tiller presents a higher percentage of structural tissues andwith a higher stage of development, as well as a lower percentage ofphotosynthetic tissues. The apical portion of the elephant grass tiller has ahigher percentage of photosynthetic tissues and a lower percentage ofstructural tissues and a higher stage of development compared to thebasal portion of the tiller.